Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1177/1758834012458137
|View full text |Cite
|
Sign up to set email alerts
|

The changing landscape in the treatment of metastatic castration-resistant prostate cancer

Abstract: Abstract:The past few years have brought increasing advances in the therapeutic management of metastatic castration-resistant prostate cancer with the approval of several agents, including vaccine therapy with sipuleucel-T, second-line chemotherapy with cabazitaxel, the bone-targeted pharmaceutical denosumab, and the novel antiandrogen therapy abiraterone acetate. There are ongoing developments with other agents in the pipeline such as MDV3100 and alpharadin that have shown promising results. This review descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…41 These new therapies have ameliorated the overall survival of patients from 6-10 months to up to 24 months for certain therapies. 43,44 Despite these clinical improvements, it is clear that additional therapeutic advances are needed. Recent studies have demonstrated that the progression of CRPC and the development of resistance to current treatments were associated with an increased activity of tyrosine kinase signaling.…”
mentioning
confidence: 99%
“…41 These new therapies have ameliorated the overall survival of patients from 6-10 months to up to 24 months for certain therapies. 43,44 Despite these clinical improvements, it is clear that additional therapeutic advances are needed. Recent studies have demonstrated that the progression of CRPC and the development of resistance to current treatments were associated with an increased activity of tyrosine kinase signaling.…”
mentioning
confidence: 99%
“…Several recommendations have been made to effectively sequence these agents. We have proposed a schema that looks at overall disease burden and presence or lack of symptoms as a guide for choice of therapy [4,11]. The National Cancer Comprehensive Network (NCCN) algorithm takes into account the presence of symptoms and stratifies whether one should receive docetaxel for symptomatic disease versus sipuleucel-T or abiraterone acetate for asymptomatic disease [12].…”
Section: History Of Drug Development Approvals and Treatment For Mcrpcmentioning
confidence: 99%
“…15,16 Since 2010, five new agents have been approved by the US FDA, namely, the CYP17 lyase inhibitor abiraterone acetate, the antiandrogen enzalutamide, the T-cell activator sipuleucel-T, the microtubule stabilizer cabazitaxel, and the radiopharmaceutical radium−223. 17,18 Given the emergence of these new agents and the increased use of bone-targeted therapies (bisphosphonates and denosumab) in standard practice, the rate of reported SREs has been steadily declining. 19 This review will describe the bone-targeted therapies in mCRPC (see Table 1) and provide insight into their current and future use.…”
Section: Targeting Bone Metastases In Metastatic Castration-resistantmentioning
confidence: 99%